Sınıf öğretmenleri ile özel eğitim öğretmenlerinin kaynaştırma eğitimi ile ilgili tutumlarının karşılaştırılması - Ekşi, Kezban (My University, 2010)
Comparision of the primary school teachers and special education teachers related to the attidutes about integration education to study the scope of basic education, integration and mainstreaming the training season. Study of classroom teachers and special education teachers' attitudes and practices of mainstreaming is intended to reveal. In this context, the universe of academic research to be done in the Anatolian side of Istanbul Pendik, Maltepe, Kadıköy, Sultanbeyli, Tuzla district, elementary schools and teachers of special education and rehabilitation of schools has created. Personal information in order to collect data form (12 questions) and to integrate the attitude scale (30 questions) was used. Applied to the subjects of the information obtained from surveys will be coded to a computer loaded with the help of Excel and SPSS Statistical analysis of data statistical software was used. Anova analysis of the data used in the analysis of scientific statistics. As a result of the independent sample t test, t = -9.965 and the significance value of 0.000 in column p <0.05 as calculated. This case of primary school teachers and special education teachers' attitudes is the difference between their attitudes (α = 0.05). Mmainstreaming of special education teachers' attitudes about the implementation, by teachers is more positive. Key words: Education, Mainstreaming, Mainstreaming Education, Special Education

Comparision of the primary school teachers and special education teachers related to the attidutes about integration education to study the scope of basic education, integration and mainstreaming the training season. Study of classroom teachers and special education teachers' attitudes and practices of mainstreaming is intended to reveal. In this context, the universe of academic research to be done in the Anatolian side of Istanbul Pendik, Maltepe, Kadıköy, Sultanbeyli, Tuzla district, elementary schools and teachers of special education and rehabilitation of schools has created. Personal information in order to collect data form (12 questions) and to integrate the attitude scale (30 questions) was used. Applied to the subjects of the information obtained from surveys will be coded to a computer loaded with the help of Excel and SPSS Statistical analysis of data statistical software was used. Anova analysis of the data used in the analysis of scientific statistics. As a result of the independent sample t test, t = -9.965 and the significance value of 0.000 in column p <0.05 as calculated. This case of primary school teachers and special education teachers' attitudes is the difference between their attitudes (α = 0.05). Mmainstreaming of special education teachers' attitudes about the implementation, by teachers is more positive. Key words: Education, Mainstreaming, Mainstreaming Education, Special Education
Keywords: İlköğretim_Öğretmenler; Kaynaştırma Eğitimi; Özel Eğitim